Prevalence of ventilator-associated pneumonia and bacterial isolates in mechanically ventilated dogs - Dreese, Kaitlyn; Wolf, Jacob (Frontiers in Veterinary Science, 2025)
IntroductionMechanical ventilation is used to treat respiratory failure in veterinary patients. Ventilator-associated pneumonia (VAP) is a reported complication of mechanical ventilation in both human and veterinary medicine. VAP can lead to increased length of mechanical ventilation, longer hospital stays, and increased mortality. While there are no gold-standard diagnostic criteria, the CDC has proposed surveillance guidelines for human medicine. A modified version of these guidelines has been created for veterinary medicine. The goal of our study was to determine the prevalence of VAP according to the CDC VAP surveillance guidelines, the modified veterinary guidelines, and clinician suspicion.MethodsThe medical records at an academic institution were searched for patients mechanically ventilated over 24 h.ResultsNone of these patients met the CDC VAP surveillance guidelines or the modified guidelines for veterinary medicine. Twelve of 71 cases were concerning for possible VAP based on clinician suspicion. The most common organism grown in both the group with clinician suspected VAP and the group without was Pseudomonas aeruginosa, eight of which were resistant to fluoroquinolones.DiscussionIt is likely that VAP is either over or under diagnosed in this population, as the clinician suspected VAP is based on subjective criteria. Findings suggest that avoiding fluoroquinolones may be beneficial when selecting an empiric antibiotic for cases in which VAP is suspected. Future studies should assess adaptions to the modified VAP surveillance guidelines for veterinary medicine because having guidelines that are too strict could eliminate cases altogether.